Nurses' knowledge about assistance in urinary tract dysfunction after spinal cord injury - Inacia Sátiro Xavier de França; Ellen Thaís Graiff de Sousa; Alexsandro Silva Coura; Lorita Marlena Freitag Pagliuca; Francisco Stélio de Sousa; Sérgio Ribeiro dos Santos (Universidade Federal do Ceará, 2019)
Objective: to report the knowledge of nurses about nursing care to people with spinal cord injury and urinary tract dysfunction. Methods: a cross-sectional study with 19 nurses from a tertiary hospital. Data were collected using a semi-structured questionnaire, validated concerning content for this research, containing sociodemographic, professional and knowledge variables. The Chi-square, Fisher and Contingency Coefficient tests were performed. Results: a higher frequency of correct responses was detected for catheterization of delay associated with a higher risk of infection (p<0.001); complications due to changes in micturition pattern (p<0.001); and discouragement to liquid intake at night (p<0.005). There was a lower percentage of correct answers for the orientation of Credé and Valsalva maneuvers (p<0.001). The training institution of participants was associated with knowledge (p=0.032). Conclusion: the participating nurses presented satisfactory knowledge about nursing care to people with spinal cord injury and urinary tract dysfunction.